Nano-sized ZrO2 derived from metal–organic frameworks and their catalytic performance for aromatic synthesis from syngas. Issue 11 (20th May 2019) - Liu, Jingge; He, Yurong; Yan, Linlin; Li, Ke; Zhang, Chenghua; Xiang, Hongwei; Wen, Xiaodong; Li, Yongwang
Abstract : Oxygen vacancies apparently improve the surface properties of nano-sized ZrO2, inducing the promotion of the catalytic performance of nano-sized ZrO2 . Abstract : Oxide–zeolite bi-functional catalysts have shown promising potential in syngas aromatization. In the hydrogenation phase, the size effect of metal oxides needs to be researched. Herein, a series of tetragonal ZrO2 with crystal sizes ranging between 4.0 and 11.3 nm was successfully prepared using UiO-66 as precursors, and it was found that the CO conversion and the methanol selectivity over ZrO2 decreased, whereas the crystal size increased. After thorough characterization by X-ray diffraction, thermogravimetric analysis, transmission electron microscopy, N2 adsorption, pyridine-adsorbed infrared spectroscopy, temperature-programmed desorption of NH3 /CO/H2, temperature-programmed reduction of H2, X-ray photoelectron spectroscopy and electron paramagnetic resonance, we found that oxygen vacancies existed on the nano-sized ZrO2 surface, which showed Lewis acidity, and the acid amount and the acid strength increased over the nano-sized ZrO2 surface: the acid amount reached 345.62 μmol g −1 with 9.26% strong acid sites over the minimum-sized ZrO2 . Density functional theory calculations were also carried out and the results demonstrated that the oxygen vacancies were beneficial for CO adsorption and activation; therefore, the minimum-sized ZrO2 showed best CO conversion with abundant methanol produced. After physical mixing with H-ZSM-5, this bi-functional catalyst exhibited 11.67% CO conversion with the aromatics selectivity as high as 94.89% for C5 + . Furthermore, no obvious deactivation was observed during a 120 h stability test.